Dynamics and Issues in Land Administration Systems in South South Cities, Nigeria - Mbee , Mbee; Joseph, Tonte (International Journal of Environmental Sciences, 2023)
Purpose: The land administration system in Nigeria has undergone changes over the years. The quest for a sustainable land administration system is borne out of the interest associated with land ownership. This study investigates the dynamics and issues that affect the land administration system in the south-south geopolitical zone, of Nigeria. Methodology: A survey research method was used in the study. Registered practicing planners constituted the study population and the data for the study were gathered using a questionnaire and secondary data. There were 522 registered practicing town, planners, in the south-south geo-political region at the time of this study and the researchers adopted a census of all the planners as participants in the study. However, only 414 of the censused population correctly filled out and returned copies of the questionnaire. Both qualitative and quantitative tools were used in analyzing the data. Findings: This study demonstrates that political interference, cultural practice, institutional frameworks, finance, existing laws, data quality, manpower and adoption of standards threaten the land administration system in south south geopolitical zone, of Nigeria. However, the financial constraint has the highest mean score of 3.40 and ranks first among the various challenges while data quality scored 2.97 and ranked 7th position among the several issues confronting the land administration system. As revealed by the study, institutional framework and existing laws in the land both ranked 6th position with a mean score of 3.18. The study empirically showed that there is no significant difference in the challenges of land administration systems in by states since the p-value (0.372) is greater than the critical level of alpha (0.05). Unique Contribution to Theory, Practice and Policy: To enhance the smooth administration of land in Nigeria, the study recommended that government should adequately fund the agencies that are statutorily saddled with the responsibility of designing land administration systems to guarantee interest in land and promote urban development.